2019
DOI: 10.21873/invivo.11757
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of microRNA-375-3p Is Not a Reliable Biomarker of Teratoma

Abstract: Background/Aim: Clinical management of testicular germ cell tumours (GCT) is based upon the measurement of serum tumour markers. Recent studies have shown that the microRNA-371a-3p is a sensitive and specific serum biomarker for all subgroups of GCT, except teratoma. To close the diagnostic gap relating to teratoma, serum levels of microRNA-375-3p have recently been suggested to represent a specific serum marker of this histological subgroup. In the present study, we tested this hypothesis. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…A recent study from Nappi et al [15] investigating the use of plasma miR-375 in combination with miR-371a-3p reported optimistic results, with an area under the ROC curve of 0.95 and 0.77 in the discovery and validation sets, respectively. However, several studies examining miR-375 alone in the context of teratoma have found no utility [7,16,17]. Our group confirmed these results and also found no serum miRNAs predictive for teratoma by small RNA sequencing [18].…”
supporting
confidence: 83%
“…A recent study from Nappi et al [15] investigating the use of plasma miR-375 in combination with miR-371a-3p reported optimistic results, with an area under the ROC curve of 0.95 and 0.77 in the discovery and validation sets, respectively. However, several studies examining miR-375 alone in the context of teratoma have found no utility [7,16,17]. Our group confirmed these results and also found no serum miRNAs predictive for teratoma by small RNA sequencing [18].…”
supporting
confidence: 83%
“…However, teratoma does not express miR‐371a‐3p 22 . Although miR‐375 was reported to be present in teratoma, 24 Belge et al 25 reported that serum miR‐375‐3p levels of patients with teratoma were not different from those of patients with GCT or controls. Further microarray studies to search for novel markers for teratoma are required.…”
Section: Discussionmentioning
confidence: 98%
“…Belge et al reported about serum miR375 in 21 patients with teratoma, 12 patients with other GCT, and 12 control samples (67). The levels of miR375 were not different between teratoma and other GCT patients or controls.…”
Section: Limitations Of Mir371mentioning
confidence: 97%